The Effect of Motivation and Job Satisfaction on the Performance of Employees at the Makassar Region V Airport Authority Office - Rahmat Rahmat; Nurmadhani Fitri Suyuthi; Mujahid Yunus (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The performance of employees is a critical factor that defines the success of the organization, especially in the case of the agencies of the public service, which require greater efficiency and professionalism. However, the achievement of ideal performance cannot be separated with the role of motivation of work and job satisfaction of each employee. This paper aims to explore and examine the impact of work motivation and job satisfaction on employee performance at the Makassar Regional Airport Authority Office, both on a partial and simultaneous basis. The quantitative research design was selected, and the multiple linear regression analysis was used. The process of acquiring data was based on a structured questionnaire, which was administered to all the employees, with the help of a saturated sampling strategy. The outcomes of the analysis indicate that work motivation has a positive and significant influence on the employee performance, and job satisfaction has a positive and significant influence as well. The improvement in employee performance is more pronounced when both variables are taken together that is evidenced by an adjusted R-squared of 68.6. These results indicate that the role of employee motivation and satisfaction on organizational performance is significant and, therefore, the management of institutions must focus on developing methods that can enhance intrinsic and extrinsic motivation and the establishment of work environments that promote employee satisfaction to guarantee continued enhancement of organizational performance.